Unknown syndrome. A possible new X linked retardation syndrome: dysmorphic facies, microcephaly, hypotonia, and small genitalia. Issue 5 (May 1990) - Porteous, M E; Burn, J
Abstract : The proband, the first child of unrelated parents, was noted in infancy to have microcephaly, developmental delay, dysmorphic facies, hypotonia, a small penis with cryptorchidism, and a fixed flexion deformity of his left index finger. His maternal uncle is severely retarded and has similar dysmorphic facies.